2022
DOI: 10.1371/journal.pone.0262290
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hypertension and non-obstructive coronary artery disease in chronic coronary syndrome (the NORIC registry)

Abstract: Background The burden of non-obstructive coronary artery disease (CAD) in the society is high, and there is currently limited evidence-based recommendation for risk stratification and treatment. Previous studies have demonstrated an association between increasing extent of non-obstructive CAD and cardiovascular events. Whether hypertension, a modifiable cardiovascular risk factor, is associated with extensive non-obstructive CAD in patients with symptomatic chronic coronary syndrome (CCS) remains unclear. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In agreement with our results in a study on 1138 patients, 45% of the individuals were hypertensive and had higher calcium scores and comorbidities than normotensive patients. Thus, there is a marked association between the Onset of Hypertension and the incidence of Cardiovascular Diseases (15).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results in a study on 1138 patients, 45% of the individuals were hypertensive and had higher calcium scores and comorbidities than normotensive patients. Thus, there is a marked association between the Onset of Hypertension and the incidence of Cardiovascular Diseases (15).…”
Section: Discussionmentioning
confidence: 99%
“…Plaque volume (mm 3 ), vessel volume (mm 3 ), and vessel length (mm) were obtained for all coronary artery segments. Plaque distribution was scored as segment involvement score (SIS), and extensive coronary artery disease defined as SIS > 4 [17] . In addition, visually identifiable coronary artery lesions were co-registered using anatomical landmarks such as distance from the ostium and subdivisions of the coronary vessels.…”
Section: Methodsmentioning
confidence: 99%
“…Systemic arterial hypertension (SAH) is the most prevalent factor in 45 to 59% of cases. 4,5 The development of secondary left ventricular hypertrophy (LVH) is associated with symptomatic myocardial ischemia even without coronary lesions. 6 Bairey Merz et al 3 reported that SAH can also influence myocardial perfusion through vasomotor alterations, endothelial dysfunction (ED), atherosclerosis, and poor vascular autoregulation capacity due to remodeling or hardening of the coronary microvasculature, which together with the deregulation of the aortic-ventricular coupling and subendocardial hypoperfusion contribute to CMD.…”
Section: Pathophysiologymentioning
confidence: 99%